2014
DOI: 10.1016/j.neuroimage.2013.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Fatal attraction: Ventral striatum predicts costly choice errors in humans

Abstract: Animals approach rewards and cues associated with reward, even when this behavior is irrelevant or detrimental to the attainment of these rewards. Motivated by these findings we study the biology of financially-costly approach behavior in humans. Our subjects passively learned to predict the occurrence of erotic rewards. We show that neuronal responses in ventral striatum during this Pavlovian learning task stably predict an individual's general tendency towards financially-costly approach behavior in an activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…3), being more specifically recruited when participants performed an action (e.g., pressing a button) in response to cues predicting reward (O'Doherty et al 2004;Tricomi et al 2004). While dorsal striatum activity has been linked to the encoding of action values used in action selection during reward-seeking behaviors (FitzGerald et al 2012), ventral striatum activity has been shown to correlate with participant's passive viewing responses to conditioned stimuli (Chumbley et al 2014). This observation is in line with the actor-critic model (Sutton and Barto 1998), suggesting that the dorsal striatum can serve a potential function of an "actor" that facilitates action selection, whereas the ventral striatum can serve as a "critic" to guide future reward attainment (O'Doherty et al 2004).…”
Section: Using Fmri To Study Reward Processing In the Striatummentioning
confidence: 99%
“…3), being more specifically recruited when participants performed an action (e.g., pressing a button) in response to cues predicting reward (O'Doherty et al 2004;Tricomi et al 2004). While dorsal striatum activity has been linked to the encoding of action values used in action selection during reward-seeking behaviors (FitzGerald et al 2012), ventral striatum activity has been shown to correlate with participant's passive viewing responses to conditioned stimuli (Chumbley et al 2014). This observation is in line with the actor-critic model (Sutton and Barto 1998), suggesting that the dorsal striatum can serve a potential function of an "actor" that facilitates action selection, whereas the ventral striatum can serve as a "critic" to guide future reward attainment (O'Doherty et al 2004).…”
Section: Using Fmri To Study Reward Processing In the Striatummentioning
confidence: 99%
“…The greater the striatal response to monetary reward anticipation, the higher the positive affective response scores [56]. The greater the striatal response to cues paired with erotic images, the more likely these cues will be chosen two months later [57]. And the greater the striatal responses to images of food and sex, the greater the weight gain and sexual activity at follow-up six months later [58].…”
Section: Increased Impulsive Reward-seeking and Dopamine Responsivitymentioning
confidence: 99%
“…Inputting the within‐subject contrasts of the first‐level into the second‐level factorial design accounts for both within‐ and between‐subject variability, and thus our approach overall was one of a random‐effects GLM (Penny et al, 2007). This two‐level approach is commonly used, including by the authors of the software (SPM) used here (Chumbley et al, 2014; Henson & Penny, 2005). The factorial design specifications were implemented twice for each analysis.…”
Section: Methodsmentioning
confidence: 99%